Stuffing the ballot box : fraud, electoral reform, and democratization in Costa Rica - Lehoucq, Fabrice Edouard, 1963- (Cambridge studies in comparative politics., 2002)
"Stuffing the Ballot Box is a study of electoral fraud and reform. It focuses on Costa Rica, a country where parties gradually transformed a fraud-ridden political system into one renowned for its stability and fair elections by the mid-twentieth century. Lehoucq and Molina draw upon a unique database of more than thirteen hundred accusations of ballot-rigging to show that, independently of social structural constraints, parties denounced fraud where electoral laws made the struggle for power more competitive. They also explain how institutional arrangements generated opportunities for several executives to assemble legislative coalitions to enact far-reaching reforms. This book argues that nonpartisan commissions should run elections; it explains why splitting responsibility over election affairs between the executive and the legislature, as classical constitutional theory suggests, is a recipe for partisan rancor and political conflict." "Stuffing the Ballot Box will interest a broad array of political and social scientists, constitutional scholars, historians, election specialists, and policy-makers interested in electoral fraud and institutional reform."--Jacket